Impacts of legislative controls on private hospitals in Malaysia / Lee Kwee Heng - Lee , Kwee Heng (2017)
The commercialisation of private hospitals under a loosely regulated framework has brought forth critical issues affecting cost, equitable access and quality care. The variation of care, existence of unregistered hospitals, adverse events and the prohibitive cost culminated in the historical implementation of the prescriptive Private Healthcare Facilities and Services Act 1998 [Act 586] and Regulations 2006 to regulate all private hospitals nationwide. This study aims is to examine the impact of Act 586 on the private hospitals in Malaysia in relation to the government’s intended objectives of accessibility, equity and quality care. It is a qualitative study utilizing the case study approach. The instruments encompass key informants interviews, focus group discussions, observations, and content analysis to elicit the impact of the legislation. Fifteen private hospitals were purposively selected in the Klang Valley. A total of 130 key informants from the private and public health sectors, professional bodies, civil society, universities and patients have contributed their perceptions to this study. The empirical findings identify several emerging themes on the impact of the Act 586 on the private hospitals. These themes are interrelated and include issues on the policy, power, governance, compliance, non-compliance, cost, inequity, quality, politics and the enforcement. The study reveals the high level of state investment in the private hospitals in Malaysia. Act 586 mandates the approval and licensing of private hospitals to ensure patients’ safety and equitable access to quality care. However, there is the concern that the vast statutory powers vested in the Minister and the Director General of Health are prone to abuse and the lack of transparency. Most of the licensed private hospitals are from the developed states. The inequitable distribution of private hospitals affects the national health objectives. While the Act 586 expressed explicitly that the governance of the private hospital is to be physician-led with the person-in-charge, but in reality private hospitals are managed by corporations. There has been a mixed of outcomes in the compliance and non-compliance. Most private hospitals faced challenges but complied with the new guidelines on mandatory licensing to continue operating their businesses. Some providers have even migrated to new purpose-built hospitals to ensure good compliance system. However, non-compliance on the controversial issue of fee-splitting between the doctors and the managed care organisations remained unresolved. Although the professional fees are regulated with a Fee Schedule, but the hospital charges remained unregulated and arbitrarily exorbitant. Notwithstanding, there is evidence of opportunistic practice of some medical specialists overcharging their patients beyond the permissible limit and often with questionable justifications. Invariably, the cost of care has escalated. Particularly, the high out-of-pocket payment in the private hospitals is an inequity issue where the majority of the population may be deprived of quality care. The private hospitals have initiated their own quality initiatives albeit with the wide variations. There is no systematic dissemination of information on treatment and outcome. While the Act 586 provides adequate enforcement capacity, Ministry of Health Malaysia appears to be constrained in regulating the influential private hospitals effectively.